1987
DOI: 10.1038/ki.1987.57
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular hypertension and injury in desoxycorticosterone–salt rats on antihypertensive therapy

Abstract: Uninephrectomized male Munich-Wistar rats received either weekly subcutaneous injections of vehicle and water for drinking; injections of desoxycorticosterone (DOC) and 1% saline (SALT) for drinking; or DOC and SALT with hydrochlorthiazide, hydralazine, reserpine and KCl added. All studies were performed six weeks after UNX. At that time, rats receiving DOC and SALT alone were hypertensive and had significantly more proteinuria and morphologic evidence of glomerular injury than rats given vehicle and tap water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 19 publications
2
25
0
Order By: Relevance
“…10,11 The DOCA model is also characterized by increased plasma volume, which is most marked during the initial 6 weeks of DOCA-salt treatment, 12 and severe renal lesions that consist of segmental sclerosis and mesangial expansion in the glomeruli, vascular wall thickening, typical onion skin pattern and ultimately fibrinoid necrosis with tubular atrophy and casts, and interstitial inflammation. 2,13 In the present study, we confirmed that elevated blood pressure is the major determinant of the decrease of coronary vascular reserve in the DOCA rats. 14 Indeed, amlodipine and mibefradil reduced systemic blood pressure to the same extent.…”
Section: Discussionsupporting
confidence: 74%
“…10,11 The DOCA model is also characterized by increased plasma volume, which is most marked during the initial 6 weeks of DOCA-salt treatment, 12 and severe renal lesions that consist of segmental sclerosis and mesangial expansion in the glomeruli, vascular wall thickening, typical onion skin pattern and ultimately fibrinoid necrosis with tubular atrophy and casts, and interstitial inflammation. 2,13 In the present study, we confirmed that elevated blood pressure is the major determinant of the decrease of coronary vascular reserve in the DOCA rats. 14 Indeed, amlodipine and mibefradil reduced systemic blood pressure to the same extent.…”
Section: Discussionsupporting
confidence: 74%
“…Elevations in glomerular capillary pressure are thought to contribute to the development of proteinuria in these conditions (5,6,11,21,24,31), but the mechanisms involved are not well understood. A rise in glomerular capillary pressure may contribute to the development of renal injury by increasing the production of transforming growth factor-␤ (TGF-␤) (1,18).…”
mentioning
confidence: 99%
“…glomeruli; HET0016; N-methylsulfonyl-6-(2-propargyloxyphenyl)hexanamide; glomerular permeability to albumin; 20-hydroxyeicosatetraenoic acid; epoxyeicosatetraenoic acids HYPERTENSION-AND DIABETES-INDUCED NEPHROPATHIES are the leading causes of end-stage renal disease (3,16,22). Elevations in glomerular capillary pressure are thought to contribute to the development of proteinuria in these conditions (5,6,11,21,24,31), but the mechanisms involved are not well understood. A rise in glomerular capillary pressure may contribute to the development of renal injury by increasing the production of transforming growth factor-␤ (TGF-␤) (1, 18).…”
mentioning
confidence: 99%
“…The finding of protection against progressive chronic renal failure without an antiproteinuric effect by Eliahou et al [15] as well as by Harris et al [14] is unique. In all other studies of protection afforded by antihypertensive drugs [1,2,5,11,12], by dietary measures such as low-protein diet [23,24], low-phosphorus diet [25], or polyunsaturated fatty acid supplemented diet [26], or by other drugs such as lipid-lowering agents [27] or heparin [28], the beneficial effect was always associated with decreased proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Antihypertensive therapy has been shown to retard progressive chronic renal failure in various rat models of experimental renal disease [1][2][3][4][5][6] and also in humans with diabetic nephropathy [7,8] as well as other primary renal diseases [9][10][11]. However, in the most extensively studied model of chronic renal failure, the remnantkidney rat, the response to different antihypertensive regimens is not uniform.…”
Section: Introductionmentioning
confidence: 99%